Detection of Node Failure in Wireless Image Sensor Networks. (29th January 2012) - Mahapatro Mahapatro, Arunanshu Arunanshu; Khilar Khilar, Pabitra Mohan Pabitra Mohan
Abstract : A sequenced process of fault detection followed by dissemination of decision made at each node characterizes the sustained operations of a fault-tolerant wireless image sensor network (WISN). This paper presents a distributed self-fault diagnosis model for WISN where fault diagnosis is achieved by disseminating decision made at each node. Architecture of fault-tolerant wireless image sensor nodes is presented. Simulation results show that sensor nodes with hard and soft faults are identified with high accuracy for a wide range of fault rate. Both time and message complexity of the proposed algorithm are O ( n ) for an n -node WISN.